Experimental Study on Flow Resistance Characteristic of Corrugated Low Finned Tubes. Issue 5 (April 2020) - Ren, Bin; Pu, Zhe; Tang, Xiaoying; Lu, Hongliang; Du, Yannan; He, Aini
Abstract: The heat transfer enhancement techniques have been developed to the third generation. The most popular and successful enhancement techniques are the artificial roughness surface and helically corrugated tube. Corrugated low finned tube is a kind of helically corrugated tube with trapezoidal shape groove. In this paper, the flow resistance characteristic of corrugated low finned tubes was studied experimentally. The results showed that all the enhanced tubes had a larger friction factor than the smooth tube due to the turbulence augmentation and rotational flow produced by helical rib. Moreover, the friction factor ratios slightly increased with the raise of Reynolds number and rib height presents more significant effect on flow resistance. Finally, all the experimental data were fitted as the function of Reynolds number, Prandtl number, tube pitch and rib height. The research results can provide a foundation for designing heat exchangers using this enhancement technique.